Anchoring and chemical-bonding effects of anodic alumina microstructure on adhesion strength. Issue 1 (2018) - Nagato, Keisuke; Yamaguchi, Takumu; Nakao, Masayuki
Abstract: Adhesion is becoming increasingly important because not only steels but also aluminum and resin materials are increasingly adopted in transporter structures. However, how the microstructure and surface energy at the adhesion boundary affect the adhesion strength has not been quantitatively clarified. In this study, the microstructure and surface energy of the structure surface are controlled by anodization process and plasma treatment, respectively, and their effects on the anchoring and chemical bonding are systematically investigated by performing peel tests, microscopy of the fracture boundary, and simulation of the stress around the boundary of the microstructure.